Consumption of different animal-based foods and risk of type 2 diabetes: An umbrella review of meta-analyses of prospective studies. (September 2022) - Giosuè, Annalisa; Calabrese, Ilaria; Riccardi, Gabriele; Vaccaro, Olga; Vitale, Marilena
Abstract: We performed an umbrella review of dose–response meta-analyses of prospective studies reporting the incidence of type 2 diabetes associated with the consumption of animal-based foods. A systematic search was conducted in PubMed, Web of Science, Scopus, and Embase according to PRISMA. Thirteen meta-analyses are included in the study providing 175 summary risk ratio estimates. The consumption of 100 g/day of total or red meat, or 50 g/day of processed meat, were associated with an increased risk; RR and 95 % CI were respectively 1.20, 1.13–1.27; 1.22, 1.14–1.30 and 1.30, 1.22–1.39. White meat (50 g/day) was associated with an increased risk, but of lesser magnitude (RR 1.04, 95 % CI 1.00–1.08). A risk reduction was reported for 200 g/day of total dairy (RR 0.95, 95 % CI 0.92–0.98) or low-fat dairy (RR 0.96, 95 % CI 0.92–1.00) or milk (RR 0.90, 95 % CI 0.83–0.98), or 100 g/day of yogurt (RR 0.94, 95 % CI 0.90–0.98). No association with diabetes risk was reported for fish or eggs. In conclusions animal-based foods have a different association with diabetes risk. To reduce diabetes risk the consumption of red and processed meat should be restricted; a moderate consumption of dairy foods, milk and yogurt, can be encouraged; moderate amounts of fish and eggs are allowed.